Misdiagnosed in double primary tumors: a case report - Daru Cahayadi, Sigit; Mitchel (Indonesian Journal of Biomedicine and Clinical Sciences, 2025)
Multiple primary malignancies (MPM) refer to the presence of two or more malignant tumors that are unrelated to each other in the same individual. Double primary malignancies that occurred in the lungs and extremities were relatively rare. We present a case of lung adenocarcinoma as pseudo-lung metastasis and pleomorphic liposarcoma on the extremity. A 62 yo male chronic smoker came with a referral from another hospital with a growing mass on his thigh and some imaging that showed pulmonary metastasis. The patient underwent a transbronchial lung biopsy and wide excision for a tumor on his thigh. However, histopathological examination revealed that both malignancies originated from different cells or as primary malignant. At 8 wk post-surgery, positron emission tomography (PET) scan was performed to rule out residual pleomorphic liposarcoma or any metastasis and the result showed no residual or metastasis. We suggest that the management of MPM be more careful and disciplined, as an error in choosing a diagnosis method might harm or worsen the patient’s condition. In the case of multiple malignancies, particularly in organs with frequent metastasis sites, it is important to consider the possibility of MPM. The diagnosis and management strategy of double primary tumors was expected to provide important information for clinicians.